Continuous Integration and Continuous Deployment (CI/CD) for Web Applications on Cloud Infrastructures - Alde Alanda; Hanriyawan Adnan Mooduto; Rizka Hadelina (JITCE (Journal of Information Technology and Computer Engineering), 2022)
At this time, the application development process has experienced much development in terms of tools and the programming language used. The application development process is required to be carried out in a fast process using various existing tools. The application development and delivery process can be done quickly using Continuous Integration (CI) and Continuous Delivery (CD). This study uses the CI/CD technique to develop real-time applications using various programming languages implemented on a cloud infrastructure using the AWS codepipeline, which focuses on automatic deployment. Application source code is stored on different media using GitHub and Amazon S3. The source code will be tested for automatic deployment using the AWS code pipeline. The results of this study show that all programming languages can be appropriately deployed with an average time of 60 seconds